IMPLEMENTASI RENCANA AKSI NASIONAL PENCEGAHAN DAN PENANGGULANGAN EKSTREMISME BERBASIS KEKERASAN YANG MENGARAH PADA TERORISME - Alfrida Heanity Panjaitan; Neneng Sri Rahayu; Hamka (Journal Publicuho, 2023)
Presidential Regulation Number 7 of 2021 concerning the National Action Plan for Preventing and Combating Violent-Based Extremism that Leads to Terrorism for 2020-2024 (RAN PE)". This policy is aimed at increasing citizens' rights to feel safe from violent extremism that leads to terrorism. This research aims to analyze and determine the implementation of the National Action Plan for Preventing and Combating Violent-Based Extremism that Leads to Terrorism. This research uses a qualitative approach with primary data, namely interviews with working groups (pokja), monitoring and evaluation teams, academics, civil society, development partners and deradicalization partners. The research was conducted using 4 (four) aspects in identifying inhibiting and driving factors in policy implementation using the Edward III Model, namely Communication, Resources, Disposition and Bureaucratic Structure. The research results concluded that Communication, Resources and Disposition were the inhibiting factors in implementing RAN PE at BNPT while Bureaucratic Structure was the only supporting factor in implementing RAN PE internally at BNPT. Apart from that, through this research, strategies were found that can be used to overcome inhibiting factors. It is hoped that the results of this research will be able to provide constructive input for BNPT as an institution that has responsibility for the successful implementation of RAN PE until 2024.